Corporate Social Responsibility Disclosure as a Social Legitimacy Mechanism and Profitability on Mining Firm Value 2021-2024 - Intan Riyani Fatimah; Syahriar Abdullah; Supartini Supartini; Susilaningtyas Budiana Kurniawati (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study investigates the effect of corporate social responsibility disclosure as a social legitimacy mechanism and profitability on firm value in the mining industry. Methodology: This research employs secondary data derived from annual financial statements and sustainability reports of mining companies listed on the Indonesia Stock Exchange. A causal associative quantitative approach with purposive sampling was utilized. Data analysis involved multiple linear regression, classical assumption testing, and descriptive statistical analysis, processed using IBM SPSS Statistics software. Main Findings: The results show that corporate social responsibility disclosure has a positive and statistically significant effect on firm value in the mining sector. In contrast, profitability does not have a significant partial effect on firm value. However, when examined simultaneously, corporate social responsibility disclosure and profitability jointly have a significant influence on firm value. Novelty/Originality of this study: This study offers originality by examining corporate social responsibility disclosure based on the Global Reporting Initiative Standards 2021 as a mechanism of social legitimacy in explaining firm value in the mining sector. Using recent panel data from 2021 to 2024 in Indonesia, the findings demonstrate that corporate social responsibility disclosure plays a more decisive role than profitability in shaping firm value, particularly in industries with high social and environmental exposure.